2001
DOI: 10.1046/j.1432-1327.2001.01949.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction, separation and properties of hybrid hexamers of glutamate dehydrogenase in which five of the six subunits are contributed by the catalytically inert D165S

Abstract: In vitro subunit hybridization was used to explore the basis of putative allosteric behaviour in clostridial glutamate dehydrogenase. C320S and D165S mutant enzymes were chosen to construct the hybrid proteins. The C320S mutant protein is fully active and shows normal allosteric properties but lacks the reactive cysteine. D165S is capable of binding both glutamate and NAD 1 but is catalytically inactive. The mutant proteins were denatured separately in 4 m urea, mixed in a 5 : 1 (D165S/C320S) ratio and diluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Our laboratory has been carrying out a study of structurefunction relationships in GDH from a variety of organisms (e.g. Syed et al, 1991;Basso et al, 1995;Rice et al, 1996;Aghajanian et al, 1999Aghajanian et al, , 2003Hayden & Engel, 2001;Hayden et al, 2002;Carrigan et al, 2005), including the basis of coenzyme specificity. On focusing attention to the NADP 1 -dependent EcGDH, we became aware of the lack of reliable baseline data.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has been carrying out a study of structurefunction relationships in GDH from a variety of organisms (e.g. Syed et al, 1991;Basso et al, 1995;Rice et al, 1996;Aghajanian et al, 1999Aghajanian et al, , 2003Hayden & Engel, 2001;Hayden et al, 2002;Carrigan et al, 2005), including the basis of coenzyme specificity. On focusing attention to the NADP 1 -dependent EcGDH, we became aware of the lack of reliable baseline data.…”
Section: Introductionmentioning
confidence: 99%
“…Mutational studies have revealed that each effect can persist in the absence of the other when binding sites are disabled (e.g. [16,17]), but this does not unambiguously indicate whether the two effects rely on septe structural machinery. Recently, however, pursuit of Trp residues thought to be sensing the pH/glutamate‐dependent conformational change [14], has highlighted two, W64 and W449, which appear to provide six pairwise interactions across the trimer–trimer interface [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among the applied compounds, it was DTNB that proved the most efficient inhibitor to NADH-GDH isolated from bean leaves. Recently Hayden and Engel (2001) have shown an important role of-SH groups in coenzyme binding. Additionally, a review of relevant studies (Turano 1997) led to the conclusion that there exist two different binding sites for the substrate (2-oxoglutarate and L-glutamate) fixation into the enzyme molecule.…”
Section: Introductionmentioning
confidence: 99%